2021
DOI: 10.1093/crocol/otab049
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab, Infliximab, and Vedolizumab in Treatment of Ulcerative Colitis: A Long-Term Retrospective Study in a Tertiary Referral Center

Abstract: Background Biological therapies have changed the landscape of pharmacological management of ulcerative colitis (UC). However, a large proportion of patients do not respond to biologics, lose their response over time or present adverse drug events. This study aims to assess therapeutic response and treatment persistence to adalimumab, infliximab and vedolizumab, three agents widely used in a tertiary referral centre of Saguenay-Lac-Saint-Jean (Quebec, Canada). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…30 Besides, favorable responses with IFX were observed in biologic-naïve patients compared to biologic-experienced patients. 31 These results are consistent with our data, as we observed that IBD patients who previously used IFX or adalimumab had a lower chance of clinical and endoscopic remission. Although we have 5-ASA derivatives, immunomodulators, and corticosteroids, it is important to emphasize that anti-TNF agents were the only advanced therapies available for IBD treatment in the Brazilian public health system during this study.…”
Section: Discussionsupporting
confidence: 93%
“…30 Besides, favorable responses with IFX were observed in biologic-naïve patients compared to biologic-experienced patients. 31 These results are consistent with our data, as we observed that IBD patients who previously used IFX or adalimumab had a lower chance of clinical and endoscopic remission. Although we have 5-ASA derivatives, immunomodulators, and corticosteroids, it is important to emphasize that anti-TNF agents were the only advanced therapies available for IBD treatment in the Brazilian public health system during this study.…”
Section: Discussionsupporting
confidence: 93%
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…According to estimates from previous studies, 18-50% of anti-TNF treated UC patients did not show any improvement and 50 to 90% did not reach remission 10,11 . Moreover, 40 to 90% suffered from adverse events (AE) among which, 5-20% will be severe AE (SAE) 11,12 .…”
Section: Introductionmentioning
confidence: 89%
“…According to estimates from previous studies, 18-50% of anti-TNF treated UC patients did not show any improvement and 50 to 90% did not reach remission 10,11 . Moreover, 40 to 90% suffered from adverse events (AE) among which, 5-20% will be severe AE (SAE) 11,12 . This high variability in response to anti-TNF accentuates the need for precision medicine to limit the unnecessary exposure to ineffective molecules and occurrence of possible AE/SAE.…”
Section: Introductionmentioning
confidence: 89%